Indonesian Mid-Career EFL Teachers’ Depersonalization and its Impact on Their Well-Being: A Narrative Inquiry - Zelvy Fauzan; Nur Arifah Drajati; Kristian Adi Putra (EDULANGUE, 2023)
Well-being is an important aspect for EFL teachers that indicate their psychological and physical wellness state both in their professional and personal life. However, depersonalization that contextually happened in the workplace can negatively affect how they teach and work in the school, causing the feeling of indifference and threatening their well-being in return. On the other hand, depersonalization has been reported to be a contagion to other people, further exposing other colleagues to experiencing and feeling burned out. Questions emerged from this phenomenon, that is, how Indonesian mid-career EFL teachers’ depersonalization affects their motivation and how they employ the coping strategy to sustain motivational well-being. Using a narrative inquiry methodological approach, this study explores this phenomenon through a narrative frame with three Indonesian mid-career EFL teachers. Extensive thematic analysis showcased that Indonesian mid-career EFL teachers experienced depersonalization originating from poor colleague work ethics and inadequate leadership, causing their motivation well-being to plummet. However, the depersonalization was overshadowed by their respective sources of motivation to work as an EFL teacher. Strategies to mitigate such depersonalization were reported to be: (1) involving oneself in continuing professional development, (2) spiritual reflection, and (3) recreational rest. The study implies an indication that contextual factors such as organizational scholarship and interpersonal-collegial relationships are playing a critical role in shaping EFL teachers’ overall well-being.